2017
DOI: 10.1002/ejsp.2325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to alcohol‐related cues on racial discrimination

Abstract: Prior research has shown that exposure to alcohol‐related images exacerbates expression of implicit racial biases, and that brief exposure to alcohol‐related words increases aggressive responses. However, the potential for alcohol cue exposure to elicit differential aggression against a Black (outgroup) relative to a White (ingroup) target—that is, racial discrimination—has never been investigated. Here, we found that White participants (N = 92) exposed to alcohol‐related words made harsher judgments of a Blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This study also found that calculation-based thinking exhibited a stronger binding effect in participants who just consumed hedonic products than in participants who just consumed utilitarian products. There is abundant evidence that the activities that participants are undertaking can activate their corresponding mental state or thinking mode (e.g., Stepanova et al, 2018 ; Sussman et al, 2015 ; Zürn & Fritz, 2017 ). For example, the profits calculating tasks can facilitate participants to think about their own interests and make rational decisions (Xin & Liu, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that calculation-based thinking exhibited a stronger binding effect in participants who just consumed hedonic products than in participants who just consumed utilitarian products. There is abundant evidence that the activities that participants are undertaking can activate their corresponding mental state or thinking mode (e.g., Stepanova et al, 2018 ; Sussman et al, 2015 ; Zürn & Fritz, 2017 ). For example, the profits calculating tasks can facilitate participants to think about their own interests and make rational decisions (Xin & Liu, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In considering how the current findings fit with the larger body of research on alcohol-cue priming effects, given the very small effects observed in the current studies, it would appear prudent to be skeptical of the specific hypothesis that exposure to alcohol cues decreases positive attitudes toward racial outgroup members. Previous research has shown that, among White undergraduates, exposure to alcohol cues can enhance expression of racial bias against Blacks (Stepanova et al, 2012) and produce harsher judgments of Black experimenters (Stepanova et al, in press). The current research represented a conceptual replication and extension of those previous studies, and the current results suggest that those previous findings might be more sensitive to methodological differences across studies than was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Merely being exposed to alcohol-related cues increases the expression of racial bias (Stepanova, Bartholow, Saults, & Friedman, 2012), discrimination (Stepanova, Bartholow, Saults, & Friedman, in press), and biases toward lesbians and gay men (Greitemeyer & Nierula, 2016). Stepanova et al (2012) found that in the Weapons Identification Task (WIT; Payne, 2001) participants who were primed with alcohol-related cues were more likely to misidentify tools when preceded by Black (compared to White) faces than those primed with neutral beverage cues.…”
Section: Alcohol-related Cues and Racial Biasmentioning
confidence: 99%
“…Research on alcohol priming shows that exposure to alcohol-related cues such as alcohol-related images or words (in the absence of alcohol consumption) can increase sexual attraction, even when those cues are presented outside of conscious awareness (Friedman, McCarthy, Forster, & Denzler, 2005). Other work has shown that exposure to alcohol cues stimulates various disinhibited judgments and behaviors such as aggression (e.g., Bartholow & Heinz, 2006; Friedman, McCarthy, Bartholow, & Hicks, 2007; Subra, Muller, Bègue, Bushman, & Delmas, 2010), expression of racial biases (Stepanova, Bartholow, Saults, & Friedman, 2012, in press), and negative biases toward lesbians and gay men (Greitemeyer & Nierula, 2016). Importantly, exposure to alcohol-related cues in the environment produces similar social disinhibition effects to those that result from actual alcohol consumption (Freeman, Friedman, Bartholow, & Wulfert, 2010).…”
mentioning
confidence: 99%